Analysis of Mn-nodules from the Alps - Maurice Bourbon (PANGAEA, 1971)
The nodules from the Briançon area in the French Alps show two types of cauliflower shaped botryoidal growth. One could be diagenetic and the other purely chemical. They could also be in-situ stromatolite like in their origin but this needs to be confirmed.
Supplement to: Bourbon, M (1971): Structure et signification de quelques nodules ferrugineux, manganésifères et phosphatés liés aux lacunes de la série crétacée et paléocène briançonnaise. Comptes rendus hebdomadaires des séances de l extquotesingleAcadémie des sciences. Série D, Sciences naturelles, 273, 2060-2062, https://store.pangaea.de/Projects/NOAA-MMS/N5753554_PDF_606_608DM.pdf